PENGARUH APLIKASI AMELIORAN DARI FORMULASI LIMBAH BATUBARA (FLY ASH DAN BOTTOM ASH) DAN SAMPAH PASAR DENGAN KAPUR TERHADAP pH, KTK DAN P TERSEDIA ULTISOL DAN GAMBUT - Farah Ilham; Amsar Maulana; Bonatua Hasiholan; Ikhsan Ilham; Fetri Yulia Negsih (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2021)
The formulation of coal waste (4 million t year-1) and market waste (175.000 t year-1) is a potential development of alternative ameliorant for marginal and swamplands. The purpose of this study was to examine ameliorant formulations from coal and market waste to improve pH, available P, and CEC of Ultisols and Peat. The step I of the study used a completely randomized design with 3 replications, namely A = coal waste (100 g); B = market waste (100 g); C = 1:1 (50 g : 50 g); D = 2:1 (66.7 g 33.3 g-1) and E = 1:2 (33.3 g 66.7g-1). The step II of the study used a completely randomized design with 3 replications in 3 formulations namely: A = best formulation (100 g); B = best formulation + 10% [Ca(OH)2] (10 g 100 g-1) and C = best formulation + 10% [CaMg(CO3)2] (10 g 100 g-1). The step III of the study used a completely randomized design with 3 replications namely: A = 0 t ha-1 (0 g 500 g-1 soil); B = 10 t ha-1 (2.5 g 500 g-1 soil); C = 20 t ha-1 (5.0 g 500 g-1 soil); D = 30 t ha-1 (7.5 g 500 g-1 soil); E = 40 t ha-1 (10.0 g 500 g-1 soil) and F = 50 t ha-1 (12.5 g 500 g-1 soil). The results of the study showed that application of ameliorant formulations from coal and market waste with 10% [CaMg(CO3)2] at 50 t ha-1 increased pH, available P and CEC of Ultisols and peat, respectively by 0.60 units, 2.11 ppm P and 10.83 cmolc kg-1 on Ultisols, and 0.33 units, 2.64 ppm P and 68.86 cmolc kg-1 in peat, compared to control.